Empowering Cadres And Housewives In Household Waste Management In Batupannu Village, Mamuju District - Ridhayani Adiningsih; Ganing, Abdul (Yayasan Ahmar Cendekia Indonesia, 2025)
Community service activities in Batupannu Village, Mamuju Regency, aim to empower cadres and housewives in household waste management with the 3R principles (Reduce, Reuse, Recycle). The main problem found was the low knowledge of the community about waste segregation, with 53.2% not knowing about it. Solutions were provided through counselling, training, and provision of pilot bins. The activity involved 34 participants and resulted in a significant improvement in waste segregation knowledge and skills, with a post-test evaluation showing 71.4% of participants had improved. The distribution of eligible bins is expected to encourage the implementation of a better waste management system in households. The outputs of this activity are journal publications, video documentation, and waste management booklets, as well as contributions to a cleaner and healthier environment.